(untitled) (Fenestella. Inside Medieval Art, 2025)
Starting from the depictions of the monumental art of the City of Rome, the development of the Roman pallium from its origins is analyzed. With the help of written sources, such as the Liber Pontificalis and the texts of the Carolingian liturgists, a line of evolution of the form and liturgical value of this insignia is identified, progressively granted by the popes to eminent bishops. The history of the pallium has its roots in the dawn of the Church of Rome. The first news, in fact, dates back to 336, but in all likelihood the origins are older. The oldest surviving pallium belonged to Saint Caesarius of Arles (died in 542) and in the same century this liturgical insignia was already the central element of the Pope’s installation ceremony. The importance assumed by the pallium is evident in the artistic depictions of Rome, at least until the appearance of the tiara. In fact, as demonstrated in the contribution, the latter becomes a symbol of temporal power, while the pallium is assigned the spiritual sphere of the Bishop of Rome. In any case, the pallium will also have an important relevance later. In fact, even if the pallium progressively becomes the insignia of metropolitan archbishops, the pope will always be depicted as the source of episcopal power. It is the Pope who grants the pallium, without it the archbishop cannot exercise his ministerium. We tried to define how the pallium evolved, refuting some hypotheses developed in the past and carefully observing its presence in the images. From them it is possible to draw numerous information not only on the shape of this sign, but also on its liturgical and spiritual value.